(untitled) (World Bulletin of Public Health, 2025)
This article explores the technologies for developing creativity-related competencies in primary school students. It examines the potential of enhancing students’ creative thinking and problem-solving skills through methods such as interactive technologies, virtual learning environments, gamified education, and project-based activities. The article emphasizes that integrating modern technologies into the educational process can improve students’ creativity and independent thinking abilities.